Pengukuran Kinerja Badan Amil Zakat Nasional (BAZNAS) Kabupaten Sukoharjo dengan Pendekatan Indeks Zakat Nasional (IZN) Pada Dimensi Makro Tahun 2021 - Dewi Kresno Murti (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
This research measures performance using a macro-dimensional index approach based on the National Zakat Index to find out whether BAZNAS Sukoharjo Regency has a good performance. This research is a descriptive quantitative research. The data in this research were obtained through interviews, documentation, and literature studies from previous research. Data analysis in this study uses the Multi Stage Weighted Index method. The results of the calculation of the performance of the Sukoharjo Regency BAZNAS calculated based on the National Zakat Index received a score of 0.474 which means it is quite good. This shows that the Sukoharjo Regency BAZNAS has a local regulation on ZIS management so that the regulation indicator gets a value of 1 which means very good. BAZNAS Sukoharjo Regency also received an allocation of APBD funds in 2021 of IDR. 200,000,000 with operational costs of IDR. 742,675,494 so that the APBD indicator received a score of 0.25 which means it is not good. The institutional database indicator received a score of 0.2475 which means it is not good.